Multidisciplinary Collaborative Care for Depressive Disorder in the Occupational Health Setting: design of a randomised controlled trial and cost-effectiveness study - Beekman Aartjan TF; Anema Johannes R; Vlasveld Moniek C; van Mechelen Willem; Hoedeman Rob; van Marwijk Harm WJ; Rutten Frans F; Roijen Leona; Feltz-Cornelis Christina (BMC, 2008)
Abstract Background Major depressive disorder (MDD) has major consequences for both patients and society, particularly in terms of needlessly long sick leave and reduced functioning. Although evidence-based treatments for MDD are available, they show disappointing results when implemented in daily practice. A focus on work is also lacking in the treatment of depressive disorder as well as communication of general practitioners (GPs) and other health care professionals with occupational physicians (OPs). The OP may play a more important role in the recovery of patients with MDD. Purpose of the present study is to tackle these obstacles by applying a collaborative care model, which has proven to be effective in the USA, with a focus on return to work (RTW). From a societal perspective, the (cost)effectiveness of this collaborative care treatment, as a way of transmural care, will be evaluated in depressed patients on sick leave in the occupational health setting. Methods/Design A randomised controlled trial in which the treatment of MDD in the occupational health setting will be evaluated in the Netherlands. A transmural collaborative care model, including Problem Solving Treatment (PST), a workplace intervention, antidepressant medication and manual guided self-help will be compared with care as usual (CAU). 126 Patients with MDD on sick leave between 4 and 12 weeks will be included in the study. Care in the intervention group will be provided by a multidisciplinary team of a trained OP-care manager and a consultant psychiatrist. The treatment is separated from the sickness certification. Data will be collected by means of questionnaires at baseline and at 3, 6, 9 and 12 months after baseline. Primary outcome measure is reduction of depressive symptoms, secondary outcome measure is time to RTW, tertiary outcome measure is the cost effectiveness. Discussion The high burden of MDD and the high level of sickness absence among people with MDD contribute to the relevance of this study. The intervention is an innovative approach, with trained OPs in a new role as care managers in the treatment of MDD. If this intervention proves to be cost-effective, implementation will be very relevant for individual patients as well as for society. Trial registration ISRCTN78462860